TELMISARTAN IN CARDIOVASCULAR RISK REDUCTION - О. D. Ostroumova; A. I. Kochetkov; E. A. Smolyarchuk; Т. I. Koniev (Кардиоваскулярная терапия и профилактика, 2018)
The article is focused on the issues of clinical efficacy of telmisartan — angiotensin II type 1 receptor blocker from the perspective of its influence on cardiovascular risk in systemic hypertension patients. The results presented, of a variety of studies, witnessing potent antihypertensive and protective properties of telmisartan. The opportunities described, for usage of the drug in high risk patients, its efficacy in cardio- and nephroprotection. Special attention is paid for an exclusive property of telmisartan to be an agonist of PPAR γ-receptors, hence to correct glucose and lipid metabolism in patients with metabolic syndrome and diabetes.